2018
DOI: 10.1787/07dcb05c-en
|View full text |Cite
|
Sign up to set email alerts
|

Synergies and trade-offs between adaptation, mitigation and agricultural productivity

Abstract: This paper is published under the responsibility of the Secretary-General of the OECD. The opinions expressed and the arguments employed herein do not necessarily reflect the official views of OECD countries. The publication of this document has been authorised by Ken Ash, Director of the Trade and Agriculture Directorate. The statistical data for Israel are supplied by and under the responsibility of the relevant Israeli authorities. The use of such data by the OECD is without prejudice to the status of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 12 publications
(12 reference statements)
0
4
0
Order By: Relevance
“…Lankoski (2016 [46]) developed a theoretical framework and empirical illustration using data from Finland to analyse the cost-effectiveness of voluntary agri-environmental programmes focussing on biodiversity conservation. This work compared a variety of payment systems: uniform payments; three types of conservation auctions with environmental targeting; uniform payment with environmental targeting; and two types of differentiated payments with environmental targeting.…”
Section: Cost-effectiveness Of Agri-environmental Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lankoski (2016 [46]) developed a theoretical framework and empirical illustration using data from Finland to analyse the cost-effectiveness of voluntary agri-environmental programmes focussing on biodiversity conservation. This work compared a variety of payment systems: uniform payments; three types of conservation auctions with environmental targeting; uniform payment with environmental targeting; and two types of differentiated payments with environmental targeting.…”
Section: Cost-effectiveness Of Agri-environmental Policiesmentioning
confidence: 99%
“…This work compared a variety of payment systems: uniform payments; three types of conservation auctions with environmental targeting; uniform payment with environmental targeting; and two types of differentiated payments with environmental targeting. The author found that "cost-effective policy design to address heterogeneous agricultural and environmental conditions requires the combination of differentiated payment level and environmental targeting" (p. 31 [46]). Across the payment systems analysed, uniform payments were found to be less efficient than other payment types, and auctions with environmental targeting are the most efficient.…”
Section: Cost-effectiveness Of Agri-environmental Policiesmentioning
confidence: 99%
“…Their assessment provides a report on the achievement of targets under the three directives, via trends in application and outcome indicators, and discusses how policies helped or not to get there, assessing the cost and benefits of policies. Lallouette, Magnier and Barreau (2016 [82]) reviewed the implementation of the EU Nitrates Directive in France from 2012-15, looking at trends in regional water quality indicators, policy changes, but also enforcement measures and their progress. 23 Initially the goal was to reach this status by 2015, with exceptions going to 2021 and potentially 2027.…”
Section: Po5 Comprehensive Assessment Combining Qualitative and Semi-quantitative Informationmentioning
confidence: 99%
“…Similarly, the majority of studies examining environmental impacts of coupled support do not distinguish between different types of coupled support, and so are again discussed together in Section 2.4. One article which looks specifically at the environmental impacts of policy-driven changes in agricultural commodity prices (including but not limited to payments based on commodity outputs) is Langpap and Wu (2011 [68]). This study uses the example of corn for ethanol in the United States (Midwest), and combines economic and biophysical models to explore the way changes in the price of agricultural commodities impact land use and cropping decisions, and how such decisions in turn have an impact on the environment.…”
Section: A2 Payments Based On Commodity Outputmentioning
confidence: 99%